Estimasi Waktu Kematian Janin Intrauterine: Sebuah Kajian Literatur - Hendri Tanjaya (Universitas Udayana, 2025)
The fetal death rate is still very high worldwide. In the field of forensics, it is important to know how to diagnose and estimate the time of fetal death. This literature review summarizes forensic evidence regarding fetal death to assess methods that can be used to estimate the time of fetal death. A search was conducted in three journal databases with the keywords (“intrauterine fetal death” or “IUFD” or stillbirth) and (maceration or autopsy or histopathology or macroscopic or microscopy or radiology or ultrasonography or USG), which were then further selected according to inclusion and exclusion criteria. The results of various studies show that ultrasound examination, by observing the last documented fetal viability and the date when the fetus was first diagnosed as deceased, macroscopic examination with reference to the maceration process, and microscopic examination of histological specimens with hematoxylin and eosin staining can be performed to estimate the time of fetal death. Among the various methods, many researchers consider microscopic examination of histological specimens to be the most reliable parameter, but bias may occur in some cases, such as in hydrops fetalis, local effusion, and sepsis.